Desigualdade socioespacial e pandemia da COVID-19 na conurbação Belém-Ananindeua-Marituba, Pará - Felipe Garcia Passos (Confins)
This paper aims to highlight the socio-spatial inequality of the Belém-Ananindeua-Marituba conurbation, relating it to the context of the novel coronavirus pandemic. The investigation was carried out by comparing maps of social indicators such as income, race, and gender and by analyzing the relationship between the location of the health care centers for patient observation and hospitalization and the subnormal clusters. The analysis shows repeated spatial patterns reflecting the indicators, with an overlap of negative bands in the same parts of the territory and the best indices in complementary areas, revealing the socio-spatial inequality existing in the conurbation, which is neglected by the policies that could make social distancing possible.